Romeo before Romeo: Notes on Shakespeare Source Study - Bigliazzi, Silvia (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2020)
The article examines a peculiar case of discontinuity in the linear transmission of the story of Romeo and Juliet before Shakespeare. Firmly situating the discussion within recent debates on source study, it argues for the interpretation of Shakespeare’s sources as products of a broad and multilayered intertextuality, identifying different ways in which linearity may give way to complex processes of textual transformation. In refashioning gender issues with a particular focus on Romeo’s ambiguous masculinity, the novellas suggest alternative genetic dynamics, prompting study of how the authors in the source-chain read their own sources and were being read in turn. The discussion challenges orthodox genetic views while inviting further reflection on the idea itself of source. Keywords: Romeo and Juliet, Source study, Masculinity, Intertextuality, Novellas